The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14095123
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Durability and Service of Asphalt Pavements through Regionalization Methods: A Case Study in Baja California, Mexico

Abstract: The objective of this research is to develop a pavement design procedure that allows calibrating the design variables of asphalt pavements using regionalized conditions, to obtain efficient pavement performance for developing countries with limited resources and data. This study analyzes the roads of the state of Baja California, Mexico; where type structures are determined and the performance grade of the binder used in the manufacture of asphalt concrete is regionalized according to the weather conditions al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The primary considerations in the highway engineering industry involve the durability and resilience of road pavements [1,2]. Several challenges frequently result in problematic pavement performance issues, such as environmental elements, heavy traffic loads, and changing climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The primary considerations in the highway engineering industry involve the durability and resilience of road pavements [1,2]. Several challenges frequently result in problematic pavement performance issues, such as environmental elements, heavy traffic loads, and changing climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[14]. Much research on the fatigue and rutting problem of asphalt pavement design has been conducted [15][16][17][18][19][20][21]. At present, the gradation design methods are conducted based on practical experience and a large number of experiments, and they do not effectively solve in advance the rutting and fatigue performance of asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors influence asphalt pavement durability on roads because the construction processes, quality of materials, design aspects, weather conditions, as well as operating conditions directly contribute to asphalt pavement durability. Most of the studies where factors that impact asphalt pavements durability are identified mainly focus on (1) traffic effects and vehicular loads, (2) characteristics and properties of the materials that make up the structure of the pavements, and (3) weather and road operation effects [4]. Under the coupled action of traffic and environmental effects, asphalt binders undergo significant physical changes such as aging, healing, and premature failure due to their sensitivity to temperature and loading rate, resulting in the early deterioration of asphalt pavement performance [5][6][7].…”
Section: Introductionmentioning
confidence: 99%